Gastrointestinal perforation: relation to corticosteroid use and COPD - a case report - Michael H.K. Nguyen; Krista M. Isaac; Rebecca Dougherty (Greater Baltimore Medical Center, 2016)
Gastrointestinal perforations are a complication of 2-10% of duodenal ulcers. There are a variety of etiologies associated with duodenal ulcer formation and its complications. Corticosteroid use is associated with an increased risk of duodenal ulcer perforation, with the first documented case in 1950. Other important medications associated with perforation include NSAIDS and opioids. Beyond medication, one of the most common disease processes, chronic obstructive pulmonary disease (COPD), has been found to be associated with peptic ulcer disease. Up to 30% of COPD patients have been found to have peptic ulcers, and COPD frequency in peptic ulcer disease is 2-3 times the general population. We herein present a case of an acute duodenal ulcer perforation in a patient receiving corticosteroid treatment for an acute COPD exacerbation.